Efforts to Improve Social Studies Learning Outcomes Through the Field Trip Learning Method in Fourth Grade Islamic Elementary School - Astuti, Dwilita; Misrodin, Misrodin (Teaching, Learning, and Development, 2025)
This research was motivated by the low social studies learning outcomes of fourth grade students at an Islamic elementary school in East Java, Indonesia. The primary objective of this study was to investigate whether the Field Trip learning method could enhance the social studies learning outcomes of fourth grade students during the 2023/2024 academic year. The study employed a Classroom Action Research (CAR) methodology, conducted over two cycles. The subjects consisted of 20 students. Data were collected through observation sheets, tests, and documentation, and were analyzed using both quantitative and qualitative approaches. The findings revealed a notable improvement in student learning outcomes. In cycle one, 10 students (50%) achieved the minimum mastery criteria, which increased to 16 students (80%) in cycle 2 demonstrating substantial progress. Based on these results, it can be concluded that the use of the Field Trip method is effective in improving student learning outcomes in social studies for fourth grade students at the studied Islamic elementary school during the 2023/2024 academic year.